Incorporation of poly(Vinyl alcohol) for the improved properties of hydrothermal derived calcium phosphate cements - Razali, Nurul Nabilah; Sopyan, Lis (Gadjah Mada University, 2018)
Calcium phosphate cement (CPC) has been synthesized via a straightforward hydrothermal route. Calcium oxide and ammonium dihydrogen phosphate were used as calcium and phosphate precursors. The precursors were refluxed in distilled water at 90–100 °C and dried overnight until the calcium phosphate powder was formed. CPC was then produced by mixing the powder and distilled water at the powder-to-liquid (P/L) ratio of 1.5. Poly(vinyl alcohol) (PVA) of 1 to 7% (w/w) was added and its effect on physical properties was investigated. It was proved that PVA addition up to 7% (w/w) has shortened the setting time but decreased the injectability. The PVA free CPC has the initial and final setting times of 71 and 187 min, respectively and the injectability of 99.92%. The compressive strength also increased with the amount of PVA added in CPC. In addition, soaking CPC in Ringer's solution for 7, 14 and 21 days also gave remarkable effects on cohesion, microstructure and mechanical properties of the cement.